The Regulatory Dilemma Between Contraceptive Promotion and Criminal Threats in Indonesia - Satriana, I Made Wahyu Chandra; Dewi, Ni Made Liana; Nuartha, Kadek Ageng; Suares, Duarte Tilman (Kosmik Hukum, 2026)
Contraceptive devices are important to be socialized to the public to prevent the transmission of dangerous diseases such as HIV and prevent pregnancy to control population growth. Promoting contraceptives can be subject to sanctions under Articles 408 and 410 of the Criminal Code with Category I fines. Therefore, officers experience a dilemma when promoting contraceptives. There is a disharmony of norms (norm conflict) between the Criminal Code and Government Regulation Number 61 of 2014 concerning reproductive health. Based on this, the problem can be formulated, namely: how to regulate actions that promote protection devices from the perspective of Ius Constitutum and how to protect actions that promote contraceptives in the Criminal Code. This type of research is normative legal research, due to the conflict of norms. the results of this research are stated in laws and regulations, including Law Number 52 of 2009 concerning Population Development and Family Development, Government Regulation Number 61 of 2014 concerning reproductive health and in Law Number 1 of 2023 concerning the Criminal Code. This issue is crucial to discuss in order to provide legal protection for contraceptive promotional tools, as the Criminal Code prohibits criminal prosecution because the officer's actions have lost their unlawful nature. This is based on the consideration that their actions, such as demonstrating the contraceptive tools, constituted the fulfillment of a state-mandated duty within the government's population program, and there are grounds for eliminating criminal penalties.